Efeito da área, da quantidade de habitat e do tipo de matriz sobre dieta de gato-maracajá (Leopardus wiedii) - Bartelega, Otávio Franco [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Since the colonization of the country many forest areas have been modified by human actions. With the breakthrough in the agriculture field there was an increasing in fragmentation and habitat loss in addition to the implantation of monocultures matrix that permeate the remaining forest fragments. This can cause changes in the availability of various resources due to species extinction, travel difficulty on the environment and access to resource. This can affect feeding patterns of certain species that lies in these spaces. For the assessment of these changes, indicator species are commonly used. The Leopardus wiedii species is a predator animal, sensitive to changes in their natural environment. Therefore, understanding how environmental changes influence its feeding habits can infer the degree of disturbance in forest fragments. At the same time, we can also better understand the pattern of occurrence and consumption of prey. In this context, this study had two objectives: (1) analyse the diet of Margay's (L. wiedii) in order to contribute with knowledge about the species that is still not much described in the literature, and (2) to correlate the food items with landscape structure in the vicinity of sampling, seeking to understand how the spatial heterogeneity can influence the feeding behaviour of this species. Stool samples were collected in eight forest fragments in the Metropolitan Region of Campinas (MRC), Sao Paulo. The samples were screened (N = 50), followed by the classification of food components into categories, including fur, feathers, reptile scales and other food items from the cat's diet. To meet the second objective, the food items found in the samples were correlated with the fragments, with the amount of forest habitats within 250, 500 and 1000 meters and the predominant matrix type in the region. Mammals (100%) were the most commonly consumed prey by Margay, followed by birds (52%) and reptiles (22%). The matrix...

Desde a colonização do país muitas áreas florestais vêm sendo modificadas por ações humanas. Com o grande avanço no campo da agricultura houve um crescente aumento da fragmentação e perda de habitat, além da implantação de matrizes de monoculturas que permeiam os fragmentos de floresta remanescentes. Isso pode causar mudanças na disponibilidade de recursos diversos, devido à extinção de espécies, dificuldade de deslocamento no ambiente e acesso à fonte de recursos. Isto pode afetar os padrões de alimentação de certas espécies residentes nestes espaços. Para a avaliação dessas alterações, são comumente utilizadas espécies indicadoras. A espécie Leopardus wiedii é um animal predador, sensível a modificações em seu ambiente natural. Logo, entendendo como as mudanças ambientais influenciam seus hábitos alimentares podemos inferir sobre o grau de distúrbios em fragmentos florestais. Ao mesmo tempo podemos ainda compreender melhor o padrão de ocorrência e consumo de suas presas. Neste contexto, este estudo teve dois objetivos: (1) analisar a dieta de gatos-maracajá (L. wiedii) a fim de contribuir com o conhecimento sobre a espécie ainda pouco descrita na literatura, e (2) correlacionar os itens alimentares com a estrutura da paisagem no entorno das amostragens, buscando entender como a heterogeneidade espacial pode influenciar no comportamento alimentar desta espécie. Amostras de fezes foram coletadas em oito fragmentos florestais na Região Metropolitana de Campinas (RMC), São Paulo. As mesmas foram triadas (N=50), seguido da classificação dos componentes alimentares em categorias, entre elas pelos, penas, escamas de répteis e demais itens alimentares da dieta do felino. Para atender ao segundo objetivo, os itens alimentares encontrados nas amostras foram correlacionados com a área dos fragmentos, com a quantidade de habitat florestal no raio de 250, 500 e 1000 metros e com o tipo de matriz predominante...
Keywords: Mamífero; Habitat (Ecologia); Paisagens fragmentadas; Habitos alimentares